CENTRAL AMERICAN COFFEE FARMERS´ MIGRATION TO THE USA: AN ANALYSIS OF THE MULTICAUSAL NATURE OF CLIMATE-DRIVEN MIGRATION (The Proceedings of The International Conference on Climate Change, 2023)
Unauthorized migration from Honduras, Guatemala, and El Salvador to the United States has become a major worldwide problem in the last 10 years. To disentangle the causes of recent Central American migration, this paper's research on the multi-causal nature of population migrations takes into account economic development, political instability, violence, and crime’s impacts, and quickly changing gender roles. Drought has lately been researched as a major driver of migration in Central America's Dry Corridor by researchers and politicians, notably among coffee farmers in the region who have been badly impacted by extreme heat and lack of rain. Climate change intensifies the effects of natural disasters, thus acting as a force multiplier. Using secondary sources, including government reports, non-governmental organizations’ briefs, and academic papers to analyze Salvadoran, Guatemalan, and Honduran coffee production, the purpose of this paper is to look into the influence of climate change as a stimulus for migration. Thousands of individuals who rely on coffee cultivation have already had their livelihoods destroyed and have been forced to migrate. With rising temperatures in the region, which is one of the most sensitive to the effects of climate change, the future is unknown. The study begins with an examination of the climate change-migration nexus, which is followed by an examination of the impacts of climate change on coffee production in this region. This paper will discuss how climatic factors along with political instability and the impact of violence explain recent Central American migration behavior to progress toward a comprehensive explanation of climate-driven migration
Keywords: climate change; migration; central america; coffee; USA